2015
DOI: 10.1159/000437439
|View full text |Cite
|
Sign up to set email alerts
|

Improved Alertness Is Associated with Early Increase in Serum Brain-Derived Neurotrophic Factor and Antidepressant Treatment Outcome in Major Depression

Abstract: Background/Aims: In major depression cognitive impairment is common and may persist despite improvement in psychopathology. So far it is unclear how closely related improvement in cognitive functioning is to the clinical course of depression. Further, it is unclear whether recovery from cognitive impairment is linked to changes in serum brain-derived neurotrophic factor (sBDNF). The objectives of this study were (1) to explore the predictive value of cognitive impairment for therapeutic outcome, and (2) to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 87 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…Whilst one small study has found an association between poorer executive function/attention performance and poor response to SNRIs ( n = 25) (21), a much larger study has found no evidence of a relationship ( n = 204) (20). …”
Section: Resultsmentioning
confidence: 99%
“…Whilst one small study has found an association between poorer executive function/attention performance and poor response to SNRIs ( n = 25) (21), a much larger study has found no evidence of a relationship ( n = 204) (20). …”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, 56 full-text articles were reviewed, of which 36 were excluded for the following reasons: (i) two studies were duplicated cohorts; (ii) five studies were reviews or meta-analyses; (iii) seven studies did not assess BDNF pre- and post- antidepressant treatment; (iv) six studies compared the BDNF val66met SNP; (v) twelve studies did not compare antidepressant medication but analyzed effects of other methods(ECT, sleep deprivation therapy, exercise et al) on BDNF; (vi) data from two studies could not be obtained; (vii) two studies did not measure BDNF, either in plasma or serum. Hence, twenty studies were ultimately included in this meta-analysis based on our inclusion criteria [ 19 , 21 39 ]. The study characteristics are displayed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Brain-derived neurotrophic factor, a member of neurotrophin family, exists in the brain, as well as in other tissue such as skeletal muscle. It plays a central role in mood disorders [26] and is associated with improved cognitive performance [27] and alertness [28]. The significant increase in BDNF with treatment of the supplement may provide mechanistic evidence for the improvement in our subjective measures of mood, such as alertness, focus, and enthusiasm.…”
Section: Discussionmentioning
confidence: 99%